Association of SLCO2B1 Genotypes With Time to Progression and Overall Survival in Patients Receiving Androgen-Deprivation Therapy for Prostate Cancer - Wang, Xiaodong (J Clin Oncol, 2016)
PURPOSE: To validate the association of three previously demonstrated SLCO2B1 germline variants with time to progression (TTP) in patients receiving androgen-deprivation therapy (ADT), and to evaluate if the SLCO2B1 genetic variants impacted overall survival (OS) for prostate cancer (PC). PATIENTS AND METHODS: Three single nucleotide polymorphisms (SNPs), exonic SNP rs12422149 and intronic SNPs rs1789693 and rs1077858, were genotyped in an independent validation cohort of 616 patients with PC who were treated with ADT at the Dana-Farber Cancer Institute from 1996 to 2013. Multivariable Cox proportional hazards regression adjusting for known prognostic factors estimated the association of these genetic variants with TTP and OS in patients receiving ADT. The expression of SLCO2B1 was examined in prostatectomy samples, and the impact of SLCO2B1 expression level on DHEAS (dehydroepiandrosterone sulfate) uptake was evaluated in cell lines. RESULTS: The association between exonic SNP rs12422149 and TTP in patients treated with ADT was confirmed in univariable (P = .019) and multivariable analyses (adjusted hazard ratio, 1.31; 95% CI, 1.00 to 1.72 for GG v AA/AG; P = .049). Because OS had not been previously evaluated, we examined the association in the combined initial and validation cohorts (N = 1,094). The intronic SNP rs1077858 was associated with OS in both univariable (P = .009; Bonferroni’s method adjusted P = .027) and multivariable analyses (adjusted hazard ratio, 1.35; 95% CI, 1.07 to 1.71 for GG v AA/AG; P = .012). SLCO2B1 expression in normal prostate tissue and in 22RV1 cells carrying the major allele of SNP rs1077858 was significantly lower than in cells carrying the risk allele. We show in vitro that SLCO2B1 expression levels correlated with DHEAS uptake by PC cells. CONCLUSION: The association of SNP rs1077858 with OS may be a result of differential SLCO2B1 expression and the consequent increased uptake of DHEAS and subsequent resistance to ADT, which, in turn, may contribute to decreased OS.